2016
DOI: 10.1007/s40264-016-0487-9
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma and Non-Melanoma Skin Cancer Associated with Angiotensin-Converting-Enzyme Inhibitors, Angiotensin-Receptor Blockers and Thiazides: A Matched Cohort Study

Abstract: A safety signal for ACEIs, ARBs, and TZs and BCC and SCC, as well as for TZs and MM, was detected. An increased awareness and education, especially for those who are at high risk for skin cancer, are warranted for patients and healthcare providers. Further exploration of such associations for these commonly used drug classes is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 19 publications
2
76
1
3
Order By: Relevance
“…Results of previous studies of ADs and the risk of skin cancer have been inconsistent . While some have shown increased risk with the use of potassium‐sparing and combination diuretics, but not loop or thiazide diuretics, several studies, including one at KPNC, have shown a significant association between thiazide diuretic use and increased SCC risk .…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous studies of ADs and the risk of skin cancer have been inconsistent . While some have shown increased risk with the use of potassium‐sparing and combination diuretics, but not loop or thiazide diuretics, several studies, including one at KPNC, have shown a significant association between thiazide diuretic use and increased SCC risk .…”
Section: Discussionmentioning
confidence: 99%
“…Phototoxic DNA damage was proven on human keratinocytes in vitro [43]. Several case studies demonstrated an enhanced sensitivity to sunlight and sunburn-like effects on patients treated with HCTs [41, 44]. In addition, the increase in photosensitivity leads to an enhanced risk of developing skin cancer and melanoma [42, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies demonstrated an enhanced sensitivity to sunlight and sunburn-like effects on patients treated with HCTs [41, 44]. In addition, the increase in photosensitivity leads to an enhanced risk of developing skin cancer and melanoma [42, 44]. Because the HCT-induced downgraded threshold of DNA damage seemed to be the leading effect of this substance, wound healing should prospectively be analyzed under application of ultraviolet light.…”
Section: Discussionmentioning
confidence: 99%
“…Of 2430 unique citations retrieved from electronic databases, 9 studies met the eligibility criteria . Additionally, the data of one conference abstract were updated in 2017; thus, we included the latest study . Finally, we included 10 observational studies, ie, 6 cohort studies and 4 case‐control studies (Figure ).…”
Section: Resultsmentioning
confidence: 99%